DEVELOPING ANIMATED VIDEO FOR LEARNING VOCABULARY: JOBS AND WORK - Febrianti, Devi; Purwanti, Indah Tri; Aruan, Rumiri Rotua (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to develop an animated learning video focused on vocabulary for jobs and work. The subjects of this study were first-year students majoring in English education at Riau University, totaling 38 students. The researchers applied Research and Development (R&D) by applying the ADDIE model. The instruments used were students need analysis questionnaires, validation sheets from media experts, material experts, and teaching experts, and student response questionnaires. The results showed that the average results of the experts' assessment for animated videos trades and professions material were 89.7% which was classified as 'highly valid', for animated videos with material collocation of words connected with work was 92.9% which was classified as 'highly valid', and for animated videos with material preparing for a job interview was 89.7% which was classified as 'highly valid', then from the results of student response questionnaires obtained a percentage score of 86.80% categorized as 'feasible' for video animations trades and professions material, a percentage score of 86.22% categorized as 'feasible' for video animation collocation of words connected with work material and 86.98% categorized as 'feasible' for video animations with material preparing for job interview. These results confirm that the animated videos are both valid and feasible to be used as vocabulary learning media for English language education students. Additionally, the study highlights that animated video media enhances student engagement and aids comprehension, suggesting a positive impact onvocabulary learning.Key Words: Development, Animated Video, Jobs and Work, Vocabulary.